Pressure pain thresholds increase after preconditioning 1 Hz repetitive transcranial magnetic stimulation with transcranial direct current stimulation. - MOLONEY, TONYA (My University, 2014)
BACKGROUND: The primary motor cortex (M1) is an effective target of non-invasive cortical stimulation (NICS) for pain threshold modulation. It has been suggested that the initial level of cortical excitability of M1 plays a key role in the plastic effects of NICS. OBJECTIVE: Here we investigate whether transcranial direct current stimulation (tDCS) primed 1 Hz repetitive transcranial magnetic stimulation (rTMS) modulates experimental pressure pain thresholds and if this is related to observed alterations in cortical excitability. METHOD: 15 healthy, male participants received 10 min 1 mA anodal, cathodal and sham tDCS to the left M1 before 15 min 1 Hz rTMS in separate sessions over a period of 3 weeks. Motor cortical excitability was recorded at baseline, post-tDCS priming and post-rTMS through recording motor evoked potentials (MEPs) from right FDI muscle. Pressure pain thresholds were determined by quantitative sensory testing (QST) through a computerized algometer, on the palmar thenar of the right hand pre- and post-stimulation. RESULTS: Cathodal tDCS-primed 1 Hz-rTMS was found to reverse the expected suppressive effect of 1 Hz rTMS on cortical excitability; leading to an overall increase in activity (p<0.001) with a parallel increase in pressure pain thresholds (p<0.01). In contrast, anodal tDCS-primed 1 Hz-rTMS resulted in a corresponding decrease in cortical excitability (p<0.05), with no significant effect on pressure pain. CONCLUSION: This study demonstrates that priming the M1 before stimulation of 1 Hz-rTMS modulates experimental pressure pain thresholds in a safe and controlled manner, producing a form of analgesia.
PUBLISHED
Keywords: Pain thresholds